A green-emitting fluorescent covalent organic framework nanostructure for visual sensing of folic acid. (December 2022) - Wen, Qiu-Lin; Wu, Bi-Chao; Pu, Zheng-Fen; Li, Rong Sheng; Ling, Jian; Cao, Qiue
Abstract: Most solid-state imine-linked covalent organic frameworks (COFs) are non-fluorescent due to aggregation-caused quenching because of strong π-π interactions and rotationally unstable imine bonds in the stacked layers of COFs. Here, we report a green-emitting fluorescent imine-based COF (ODA-TP-COF) by integrating flexible building blocks and transforming the COF into nanoscale sheets. Due to the existence of flexible non-planar units, the interlayer distance of ODA-TP-COF increases, which weakens the π-π interaction and thus reduces the aggregation-caused fluorescence quenching. Our further study found that the ODA-TP-COF dispersed in different solvents has different fluorescence properties, and surprisingly when methanol was used as the solvent for ODA-TP-COF, the presence of a small biological molecule, folic acid, could significantly and selectively induce a blue-shifts of ODA-TP-COF fluorescence peak. It is the first time that the ODA-TP-COF could serve as a highly selective fluorescent probe for the visual detection of folic acid. Graphical abstract: Image 1 Highlights: Prepared a green-emitting fluorescent imine-based COF by integrating flexible building blocks. Folic acid could significantly and selectively induce the blue-shift of the fluorescence peak of COF. It is the first time that the COF was served as a fluorescent probe for the visual detection of folic acid.